UUBE for Secure Sharing of Personal Health Records in Cloud - Dr. Dhina Suresh, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Cloud based Personal Health Record (PHR) is a prominent cloud based platform for switching a person’s health information in a secure manner. They are next generation cloud platform making possible for well organized , reliable & scalable data access to foster the public care. There happen numerous security issues when records of the data owners are reevaluated through the outsider cloud suppliers. The health records which are kept secret should be put away and recovered through a protected source with no misfortune in the information. Nonetheless sharing and probing of the data is the bottom line, but when it is outsourced beyond doubt it is a burdensome task. It might prompt reveal the delicate data thus the records may get helpless against the technocrats. In this article, we have suggested a novel access control structure called as User Usage Based Encryption (UUBE) constructed on the searchable attribute based encryption to guarantee the data protection. Utilization is planned as credential with a time span to each private attribute. The client can decipher only if there is a match between the accreditation's related with the attributes. Utilizing the feature extraction the accessible encryption plot empowers a predictable directing of encoded credits. Prior to starting the encryption conspire we apply the singular value decomposition algorithm to the non-utilized or less utilized credits to diminish the trait set. Moreover the information client privacy traps are handled utilizing the semantic grouping. To save the client secrecy a solid overlay protection convention is planned. We show a total security investigation with the goal that our suggested framework rules the cutting-edge approaches regarding communication and encoding cost.